Assessment of sperm DNA integrity and ICSI outcome after sperm cryopreservation - E.A. Hassan; S.A. Abd- Elmaksoud; T.G. Abdel-Kader; A.F. El-Sherbiny; M.A. Dkhil; R. Abdel-Gaber; D. Delic; N.M. Ibrahim (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The association between suboptimal sperm parameters and DNA damage in mature spermatozoa indicates that some individuals may have intrinsic issues with spermatogenesis. The objective of this study is to evaluate the impact of cryopreservation and reactive oxygen species (ROS) on sperm DNA stability, as assessed by Sperm Chromatin Structure Assay (SCSA) motility and viability, and ICSI Result. Participants contacted the Fertility Clinic and provided written informed consent. All data were subsequently handled and processed in a confidential and anonymous manner. There was a source of 300 participants (600 semen samples) in this study, divided into 3 groups. All female partners underwent ICSI, (some of the oocytes injected by fresh sperms and others injected by cryopreserved sperms for same patient (liquid nitrogen at−196°C, in accordance with conventional cryopreservation protocols). Cryopreservation of spermatozoa from fertile men does not seem to adversely affect sperm DNA integrity in either semen or prepared samples. However, the morphology of spermatozoa in both semen and prepared samples is significantly compromised by the cryopreservation process. No evidence that cryopreserving spermatozoa from healthy males would compromise the genetic material of the sperm either in the semen or in the laboratory-prepared samples.